2018
DOI: 10.1097/fpc.0000000000000349
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic and clinical predictors of response to clopidogrel plus aspirin after acute coronary syndrome in Egyptians

Abstract: These results highlight that CYP2C19*2, along with diabetes, and use of proton pump inhibitor and statin are important factors jointly associated with variability in clinical response to DAPT following ACS in Egyptians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Personalized medicine approaches involve the use of patient‐specific factors, including genotype data to predict optimal pharmacotherapy regimens for individual patients. To enable personalized approaches to HF therapy, pharmacogenetic research is needed to uncover genetic factors that, along with clinical factors, underlie differences in response to HF therapy . Herein, we identified genetic and clinical factors that explained a large portion of the variability in response to MRAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Personalized medicine approaches involve the use of patient‐specific factors, including genotype data to predict optimal pharmacotherapy regimens for individual patients. To enable personalized approaches to HF therapy, pharmacogenetic research is needed to uncover genetic factors that, along with clinical factors, underlie differences in response to HF therapy . Herein, we identified genetic and clinical factors that explained a large portion of the variability in response to MRAs.…”
Section: Discussionmentioning
confidence: 99%
“…To enable personalized approaches to HF therapy, pharmacogenetic research is needed to uncover genetic factors that, along with clinical factors, underlie differences in response to HF therapy. 39 Herein, we identified genetic and clinical factors that explained a large portion of the variability in response to MRAs. Specifically, baseline K and the AGT rs699 and CYB11B2 rs1799998 SNPs explained 71% and 63% of variability in ejection fraction and K post-MRA treatment.…”
Section: Genotype and Spironolactone Responsementioning
confidence: 99%
“…In 2012, the morbidity of coronary artery disease in the Uygur population of Xinjiang was 24.2%, much higher than the national average (7.2%) [ 13 ]. Polymorphisms of the CYP2C19 gene and clinical factors are strong predictors of cardiovascular outcomes for patients with acute coronary syndrome treated with oral clopidogrel [ 14 , 15 ]. Nevertheless, very little is known about the influence of such factors in Uygur populations.…”
Section: Introductionmentioning
confidence: 99%
“…They found that these patients had an almost equal to three-fold increase in 30-day incidence of major adverse cardiovascular events risk compared with non-AA homozygotes (15). However, these results were not confirmed in an Egyptian acute coronary syndrome patient treated with DAPT, which reported no association with PEAR1 rs12041331 and cardiovascular risks (21). Moreover, the Aspirin in Reducing Events in the Elderly trial analyzed the relationship between PEAR1 rs12041331 and cardiovascular outcomes in a healthy elderly population with no previous atherothrombotic cardiovascular disease (14).…”
Section: Comparison With Prior Studiesmentioning
confidence: 93%